The Role of Social Media in Developing Nonprofit Brand: A Case Study on Akademi Berbagi - Danasmoro Brahmantyo (Jurnal InterAct, 2015)
Social media as a form of development in information technology and communication has open doors for all kinds of innovations to emerge. Initiatives from the society which are present in social media have similar characteristics with the medium that forms social media, which are: open, participative, accommodating two-way conversations, and focusing in the connectivity between communities. Social media encourages the formation of identity and image of nonprofit brands as representations of movement/social organization in the era of information. Through a single case analysis case study on Akademi Berbagi, it was found that the values that are formed as a result of the interactions within the community of social movement activists become the foundation for forming and dispersing nonprofit branding messages that are genuine which comes from, made by and directed to its activists. By optimizing social media, the nonprofit branding delivers a result that is low cost and high impact. The characteristics of Akademi Berbagi as a nonprofit brand can be said to be similar to the characteristics of social media which are mentioned by Mayfield (2008), which are: openness, participation, two-way conversations and focusing on community and connectivity. As a brand that focuses on community, Akademi Berbagi has functioned as the former of social connection and reputation both for individuals and the managing volunteers through conversations and an ability to share in the internet society and the era of information.